Molecular aspects of the antagonistic interaction of smoke-derived butenolides on the germination process of Grand Rapids lettuce (Lactuca sativa) achenes - Soós, Vilmos; Sebestyén, Endre; Posta, Martin; Kohout, Ladislav; Light, Marnie E; Van Staden, Johannes; Balázs, Ervin (The New phytologist, 2012)
Smoke-derived compounds provide a strong chemical signal to seeds in the soil seed bank, allowing them to take advantage of the germination niche created by the occurrence of fire. The germination stimulatory activity of smoke can largely be attributed to karrikinolide (KAR(1) ), while a related compound, trimethylbutenolide (TMB), has been shown to have an inhibitory effect on germination. The aim of this study was to characterize the interaction of these potent fire-generated compounds. Dose-response analysis, leaching tests and a detailed transcriptome study were performed using highly KAR(1) -sensitive lettuce (Lactuca sativa cv 'Grand Rapids') achenes. Dose-response analysis demonstrated that the compounds are not competitors and TMB modulates germination in a concentration-dependent manner. The transcriptome analysis revealed a contrasting expression pattern induced by the compounds. KAR(1) suppressed, while TMB up-regulated ABA, seed maturation and dormancy-related transcripts. The effect of TMB was reversed by leaching the compound, while the KAR(1) effect was only reversible by leaching within the first 2 h of KAR(1) treatment. Our findings suggest that the compounds may act in concert for germination-related signaling. After the occurrence of fire, sufficient rainfall would contribute to post-germination seedling recruitment by reducing the concentration of the inhibitory compound.
Keywords: Lactuca; gama-butyrolakton; Dose-Response Relationship, Drug; Reproducibility of Results; vztah mezi dávkou a účinkem léčiva; Abscisic Acid; Gene Expression Profiling; Pyrans; Smoke; Gene Expression Regulation, Plant; požáry; reprodukovatelnost výsledků; kyselina abscisová; Seeds; regulátory růstu rostlin; salát (hlávkový); semena rostlinná; vegetační klid; klíčení; Plant Dormancy; pyrany; furany; Germination; regulace genové exprese u rostlin; Fires; 4-Butyrolactone; stanovení celkové genové exprese; Plant Growth Regulators; kouř; Furans